Relationship between power output and speed-related performance in Brazilian wheelchair basketball players - Loturco, I.; McGuigan, M. R.; Reis, V. P.; Santos, S.; Yanci, J.; Pereira, L. A.; Winckler, C. (Adapted Physical Activity Quarterly, 2023)
This study aimed to investigate the association between the optimum power load in the bench press (BP), shoulder press (SP), and prone bench pull (PBP) exercises and acceleration (ACC) and speed performances in 11 National Team wheelchair basketball (WB) players with similar levels of disability. All athletes were previously familiarized with the testing procedures that were performed on the same day during the competitive period of the season. First, athletes performed a wheelchair 20-m sprint assessment and, subsequently, a maximum power load test to determine the mean propulsive power (MPP) in the BP, SP, and PBP. A Pearson product-moment correlation was used to examine the relationships between sprint velocity (VEL), ACC, and the MPP in the three exercises. The significance level was set as p < .05. Large to very large significant associations were observed between VEL and ACC and the MPP in the BP, SP, and PBP exercises (r varying from .60 to .77; p < .05). The results reveal that WB players who produce more power in these three exercises are also able to accelerate faster and achieve higher speeds over short distances. Given the key importance of high and successive ACCs during wheelchair game-related maneuvers, it is recommended that coaches frequently assess the optimum power load in BP, SP, and PBP in WB players, even during their regular training sessions.